The Pareto Distribution and the Cobb-Douglas Production Function in Activity Analysis - Houthakker, H. S. (Review of Economic Studies, 1955)
Journal Article The Pareto Distribution and the Cobb-Douglas Production Function in Activity Analysis Get access H. S. Houthakker H. S. Houthakker Stanford, California Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 23, Issue 1, 1955, Pages 27–31, https://doi.org/10.2307/2296148 Published: 01 April 1955